Data-rich linguistics : papers in honor of Yiwola Awoyale - Adesola, Oluseye; Akinlabi, Akinbiyi; Orie, Ọlanikẹ-Ọla; Awóyalé, Yíwọlá (Cambridge Scholars Publishing, 2018)
This collection was compiled by an international group of scholars in recognition of Professor Yiwola Awoyale's contributions to African language and linguistic studies. Based at University of Pennsylvania, Professor Awoyale is particularly celebrated as a great field linguist, who pays special attention to data and data documentation. This edited volume presents current research on topics concerning the syntax, semantics, phonology, applied- and socio-linguistics of African languages, providing a state-of-the-art account of contemporary issues in African linguistics today.